2017
DOI: 10.1093/gbe/evx031
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Specific Expression Analysis Does Not Support Sex Chromosome Inactivation on the Chicken Z Chromosome

Abstract: Heterogametic sex chromosomes have evolved many times independently, and in many cases, the loss of functional genes from the sex-limited Y or W chromosome leaves only one functional gene copy on the corresponding X or Z chromosome in the heterogametic sex. Because gene dose often correlates with gene expression level, this difference in gene dose between males and females for X- or Z-linked genes in some cases has selected for chromosome-wide transcriptional dosage compensation mechanisms to counteract any re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…Although there is no chromosome-wide dosage compensation in chicken, Z-linked genes differ in their M:F expression ratios, with a tendency for dosage-sensitive genes to be more equally expressed between the sexes (Zimmer et al 2016), but the regulatory means through which this gene-specific dosage compensation is achieved are not fully understood (Discussion; Melamed and Arnold 2007;Mank and Ellegren 2009;Itoh et al 2010;Livernois et al 2013;Wang et al 2017). We reasoned that miR-2954-3p, with its strong male bias, broad expression, and preference for Z-linked genes might provide an alternative path to gene-specific dosage compensation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no chromosome-wide dosage compensation in chicken, Z-linked genes differ in their M:F expression ratios, with a tendency for dosage-sensitive genes to be more equally expressed between the sexes (Zimmer et al 2016), but the regulatory means through which this gene-specific dosage compensation is achieved are not fully understood (Discussion; Melamed and Arnold 2007;Mank and Ellegren 2009;Itoh et al 2010;Livernois et al 2013;Wang et al 2017). We reasoned that miR-2954-3p, with its strong male bias, broad expression, and preference for Z-linked genes might provide an alternative path to gene-specific dosage compensation.…”
Section: Resultsmentioning
confidence: 99%
“…That said, previous work has demonstrated that M:F expression ratios vary across Z-linked genes, such that the intrinsic male bias is counteracted for a subset of dosage-sensitive genes (Zimmer et al 2016), but it has not been clear how such gene-specific dosage compensation is achieved. A handful of Z-linked genes may be affected by local Z inactivation (Livernois et al 2013), although more extensive Z inactivation is not supported by patterns of allele-specific expression (Wang et al 2017). Additionally, it has been suggested that a small region of the chicken Z Chromosome might be enriched for dosage-compensated genes (Melamed and Arnold 2007), but the pattern was not recapitulated in another study (Mank and Ellegren 2009) and does not appear to be evolutionarily conserved (Itoh et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Because the occurrence of A and F ancestral blocks on sex chromosomes corresponds to either lineages without clear signals of global dosage compensation (ancestral chromosome A: sole, clawed frog, chicken) 63,68 and a lineage with global dosage compensation (ancestral chromosome F: human 69,70 ), we asked whether genes found on these two ancestral chromosomes showed different dosage sensitivity characteristics. According to this hypothesis, genes on ancestral vertebrate chromosome F, which correspond to genes on the human X, should have increased sensitivity to changes in dosage compared to the genes found on ancestral chromosome A, which are found on heteromorphic sex chromosomes in species with no global dosage compensation 63,71 . 63 and those in reptiles 22,60 , birds 64,65 , and mammals 65 ( dates from timetree.org 66,67 ).…”
Section: A Shared Origin Of Genes Present On Vertebrate Heteromorphicmentioning
confidence: 99%
“…For instance, genomic imprinting has been observed in mammals and some plants [15][16][17], but seems largely absent in birds assessed to date [18][19][20]. Dosage compensation exists in some diploid species to buffer the effect of copy number difference of genes on the sex chromosome [21][22][23], but it has been reported to be incomplete in birds [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%